Use of whole genome sequences to develop a molecular phylogenetic framework for Rhodococcus fascians and the Rhodococcus genus - Creason, Allison L.; Davis, Edward W.; Putnam, Melodie L.; Vandeputte, Olivier M.; Chang, Jeff H. (Frontiers in Plant Science, 2014)
The accurate diagnosis of diseases caused by pathogenic bacteria requires a stable species classification. Rhodococcus fascians is the only documented member of its ill-defined genus that is capable of causing disease on a wide range of agriculturally important plants. Comparisons of genome sequences generated from isolates of Rhodococcus associated with diseased plants revealed a level of genetic diversity consistent with them representing multiple species. To test this, we generated a tree based on more than 1700 homologous sequences from plant-associated isolates of Rhodococcus, and obtained support from additional approaches that measure and cluster based on genome similarities. Results were consistent in supporting the definition of new Rhodococcus species within clades containing phytopathogenic members. We also used the genome sequences, along with other rhodococcal genome sequences to construct a molecular phylogenetic tree as a framework for resolving the Rhodococcus genus. Results indicated that Rhodococcus has the potential for having 20 species and also confirmed a need to revisit the taxonomic groupings within Rhodococcus.